Advances in Donkey Disease Surveillance and Microbiome Characterization in China - Muhammad Zahoor Khan; Yan Li; Mingxia Zhu; Mengmeng Li; Tongtong Wang; Zhenwei Zhang; Wenqiang Liu; Qingshan Ma; Changfa Wang (Microorganisms)
This review article highlights the surveillance of bacterial, viral, and parasitic diseases in donkey populations in China. Key findings highlight significant threats from Equine herpesviruses (EHV-8 and EHV-1), which cause encephalitis, abortion, and respiratory distress. Several parasitic infections including Giardia duodenalis, Cryptosporidium spp., Enterocytozoon bieneusi, and Toxoplasma gondii present important zoonotic concerns across multiple regions of China. Additionally, this review synthesizes current knowledge on donkey microbiota across various body sites and examines their functional significance in health and disease. The complex relationship between the microbiota and host health represents a critical area of research in donkeys. Recent molecular advancements have enhanced our understanding of the diverse microbial ecosystems inhabiting different body sites in donkeys and their profound impact on health outcomes. As single-stomach herbivores, donkeys possess complex microbial communities throughout their digestive tracts that are essential for intestinal homeostasis and nutritional processing. Significant variations in microbiota composition exist across different intestinal segments, with the hindgut displaying greater richness and diversity compared to the foregut. Beyond the digestive system, distinct microbial profiles have been characterized across various body sites including the skin, oral cavity, reproductive tract, and body secretions such as milk. The health implications of donkey microbiota extend to critical areas including nutrition, immune function, and disease susceptibility. Research demonstrates how dietary interventions, environmental stressors, and physiological states significantly alter microbial communities, correlating with changes in inflammatory markers, antioxidant responses, and metabolic functions. Additionally, specific microbial signatures associated with conditions like endometritis and respiratory disease suggest the potential for microbiota-based diagnostics and therapeutics. The identification of antibiotic-resistant strains of Proteus mirabilis and Klebsiella pneumoniae in donkey meat highlights food safety concerns requiring enhanced monitoring systems and standardized safety protocols. These findings provide a foundation for improved donkey healthcare management, including targeted disease surveillance, microbiota-based interventions, and protective measures for those working with donkeys or consuming donkey-derived products.